CulturePad: Connecting Aboriginal children and school to Aboriginal language and culture through the use of technology - Pagram, J.; Campbell, A.; Cooper, Martin (2017)
Language is an essential feature of culture and identity, and important in instilling a sense of well-being and belonging for many Aboriginal and Torres Strait Islander people. Yet most traditional Australian languages are in serious decline, while English language literacy levels among Aboriginal children remain well below those for other Australians. The project was set in two remote Aboriginal communities in the Western Australian Kimberley region This unique project aimed to connect Aboriginal children, their community and school to local Aboriginal language and culture through the innovative use of technology, while simultaneously developing skills in standard English. An interactive digital tool known as CulturePad was developed running upon Apple iPad hardware to promote local language, English and digital literacy skills without the need for internet access. Oral and written language was captured and recorded locally and made readily shareable within and between communities. Preliminary findings have shown CulturePad sustains the interest and engagement of Aboriginal children, teachers and community-based Aboriginal educators in oral and written language development, and has great potential as a catalyst for building stronger partnerships between schools and communities and improving Aboriginal students’ engagement in education in remote areas.